Flow patterns and heat transfer coefficients using a rotational diffuser coupled with a radiant floor cooling - Fernández-Hernández, Francisco Ángel; Fernández-Gutiérrez, Alberto; Martínez-Almansa, Juan José; Del-Pino-Peñas, Carlos Manuel; Parras-Anguita, Luis (Elsevier, 2019)
In this research, we explore the characteristics of one HVAC system integrated by a rotational floor diffuser with an underfloor plenum, coupled with a radiant floor cooling. Numerical simulations are performed using a technique that allows us to divide the full spatial domain into two smaller ones. On the one hand, we mimic the diffuser outflow entering into the room using a very detailed mesh, which is simulated using a semi-sphere surface. On the other hand, we impose the inlet in the whole room with the radiant floor through the outflow in the former diffuser mesh. Besides, we carried out real scale experiments in a model room. We obtain the experimental shape of the plume near the rotational diffuser from smoke visualizations, and those are compared qualitatively to the ones obtained numerically. We show that there exist two different regimes depending on the flow rate: displacement ventilation or very active mixing process with the surrounding ambient air for low or high flow-rates, respectively. We compute the Nusselt number against Reynolds number both experimentally and numerically, and they collapse in a proposed linear fitting, thus showing that the type of flow patterns created near the diffuser does not affect the heat transfer coefficient strongly. However, we find a change in the linear slope near Reynolds number 15000, being the explanation to the existence of this critical value the variations observed in the flow patterns. Finally, we propose another general non-linear fitting of the Nusselt number as a function not only of Reynolds number but temperature differences for all the cases considered (isothermal and non-isothermal). This latter fitting shows us that only inertia controls heat transfer.
Keywords: Ingeniería de estructuras; Diseño y construcción; Rotational diffuser; Radiant floor cooling